Cenozoic plate tectonic reconstructions and plate boundary processes in the Southwest Pacific - Keller, William R. (California Institute of Technology, 2005)
The Australia-Pacific-Antarctic plate circuit has long been a weak link in global plate reconstruction models for Cenozoic time. The time period spanning chron 20 to chron 7 (43-25 Ma) is particularly problematic for global plate models because seafloor spreading was occurring in two poorly constrained regions in the Southwest Pacific - the Macquarie Basin southwest of New Zealand, and the Adare Basin north of the Ross Sea, Antarctica. I present a new shipboard dataset collected aboard several recent geophysical cruises which places important constraints on the tectonic evolution of these two regions. Utilizing multibeam bathymetry, magnetic, gravity, and seismic data in the Macquarie Basin, I am able to locate tectonic features and magnetic anomalies with greater accuracy than was previously possible. These tectonic features and magnetic anomalies are then used to calculate relative motion between the Australia and Pacific Plates for chrons 18-11 (40-30 Ma). I use revised locations of the rifted margins along the boundary of the Macquarie Basin to determine a best-fit pre-rift reconstruction for this region. During this same time period, seafloor spreading between East and West Antarctica was occurring along the Adare Trough, an extinct spreading center located north of the Ross Sea. Motion along the Adare Trough accounts for roughly 180 km of previously unrecognized motion between East and West Antarctica. I present multibeam and seismic data in the Adare Basin that place constraints on the timing and character of motion along this plate boundary.